2022
DOI: 10.1177/09673911221103317
|View full text |Cite
|
Sign up to set email alerts
|

Sisal fiber reinforced polyethylene terephthalate composites; Fabrication, characterization and possible application

Abstract: The use of thermoplastics (TPs) for natural fiber composites is restricted to commodity ones like polypropylene and polyethylene However, using engineered TPs such as polyethylene terephthalate (PET) will benefit from its technical and economic advantages. The research aims to characterize injection molded PET composites reinforced with sisal fibers treated differently. Polyethylene terephthalate composites containing 40 wt.% of untreated, alkaline-treated, and alkali/acetylation treated sisal fibers were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(373 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, the hemicellulose content of the studied fibres is at least 17 wt%, which is about 3 and 8 times higher than that ( Table 2 ) of jute and cotton, respectively. This high hemicellulose content could make the fibres hydrophilic, which is interesting for the development of absorbent textile fabrics [ 23 ], but a major drawback for the interlocking of the fibres with polymer matrices [ 11 , 33 ]. For the lignin content, which makes the fibres stiff, the values found in this study are interesting, as they are lower than those found for fibres already used for the manufacture of placemats such as soda degummed jute [ 1 ] and banana [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the hemicellulose content of the studied fibres is at least 17 wt%, which is about 3 and 8 times higher than that ( Table 2 ) of jute and cotton, respectively. This high hemicellulose content could make the fibres hydrophilic, which is interesting for the development of absorbent textile fabrics [ 23 ], but a major drawback for the interlocking of the fibres with polymer matrices [ 11 , 33 ]. For the lignin content, which makes the fibres stiff, the values found in this study are interesting, as they are lower than those found for fibres already used for the manufacture of placemats such as soda degummed jute [ 1 ] and banana [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…As studied in a separate paper by the same researchers, 38 a composite with better mechanical, thermal and water uptake properties was produced from sisal fiber and PET polymer by injection molding. There are no literature or experimental trials concerning the injection molding of sisal or any NF with PET, an engineering TP.…”
Section: Resultsmentioning
confidence: 99%
“…However, it can be understood from 38 that injection molding of natural fibers with PET is possible with some thermal effects on the fiber which could lead researchers to further investigate on the mechanisms to improve the thermal properties of sisal and other natural fibers.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the extracted bers were sun-dried, which whitened the ber. Once dried, the sisal bers were ready for the preparation of samples [19]. The extraction process of sisal ber is shown in Fig.…”
Section: Extraction and Preparation Of The Bermentioning
confidence: 99%